Overcoming High Communication Anxiety of Trainee-nurses with a Two-dimensional Approach at the Zuarungu Health Training School, Ghana - Alhassan, Azumah (Advances in Social Sciences Research Journal, 2015)
High communication anxiety (HCA) dispossesses individuals’ inter-personal communication skills that are needed in the academia and at other public places. Admittedly, research on HCA abounds but lack holistic remediation in providing a comprehensive cure. In Ghana, knowledge on how teachers can effectively manage HCA and its instruction is limited. Moreover, most teachers have limited knowledge of how instruction may be ineffective due to HCA. Interestingly, nursing is constantly evolving. And to-be-nurses who have high communication anxiety may suffer many effects while in training and in practice if their HCA is not ameliorated. Because, nurses, by the nature of their work, cannot be shy, avoid public communication or inter-personal relations that are needed in providing effective health service. This study was to actualize classroom participation in order to reduce the HCA of 50 to-be-nurses with a two-dimensional approach involving communication instruction and motivational persuasive contexts that co-constructed inter-personal communication relations. The study resulted in reducing trainees’ fear of speaking in public and great improvement in their 2014/2015 second semester GPAs.